Linear buckling of quadrangular and kagome gridshells: A comparative assessment. (1st February 2017) - Mesnil, Romain; Douthe, Cyril; Baverel, Olivier; Léger, Bruno
Highlights: A strategy for the covering of kagome meshes with planar facets. A parametric study comparing the linear buckling load of kagome lattices with quadrangular gridshells. Design guidelines for kagome gridshells. Abstract: The design of gridshells is subject to strong mechanical and fabrication constraints, which remain largely unexplored for non-regular patterns. The aim of this article is to compare the structural performance of two kind of gridshells. The first one is the kagome gridshell and it is derived from a non-regular pattern constituted of triangles and hexagons. The second one results from a regular pattern of quadrangles unbraced by diagonal elements. A method is proposed to cover kagome gridshells with planar facets, which reduces considerably the cost of fabrication of the cladding. The sensitivity of kagome gridshells to geometrical imperfections is discussed. The linearised buckling load of kagome gridshells is then compared to the one of quadrilateral gridshells. The most relevant design variables are considered in the parametric study. Two building typologies are studied for symmetrical and non-symmetrical load cases: dome and barrel vault. It reveals that the kagome gridshell outperforms quadrilateral gridshell for a very similar construction cost.